Saving Behaviour and the Effectiveness of Fiscal Policy - de Mello, Luiz (OECD Economics Department Working Papers, 2004)
This paper examines the extent to which fiscal policy actions may be offset by simultaneous, anticipatory changes in private saving, as well as the determinants of that offset. The conditions under which private agents will engage in forward-looking consumption-smoothing behaviour are quite strict and unlikely to hold fully in practice. However, based on a sample of at most 21 OECD countries spanning the period 1970-2002, there is strong evidence of partial, yet substantial, offsetting movements in aggregate private and public saving. The overall offset is estimated at between about one-third and one-half, depending on model specification, and applies both to public consumption and revenue shifts. This is consistent with a marked degree of anticipatory private sector behaviour, insofar as the ex ante saving "leakage" embedded in the pure Keynesian or IS/LM type models would be expected to be smaller and apply only to revenues and transfers. Wealth effects, as in the case of rising equity and housing prices, are found to have an important complementary impact on saving, usually in reinforcing the direct saving offset. Initial conditions, as reflected in debt/GDP ratios are also found to influence the size of the offset